Fraud Hexagon Analysis in Detecting Financial Statement Fraud with Corporate Governance as a Moderating Variable - Haeronnisa, Haeronnisa; Isnawati, Isnawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to study the influence of the fraud hexagon on financial report fraud in insurance companies listed on the Indonesia Stock Exchange from 2018 to 2022, incorporating corporate governance as a moderating factor. In this study, the fraud hexagon serves as the independent variable, while financial report fraud is the dependent variable. The data analysis method used is multiple regression. The research findings indicate that the variables of external pressure and ineffective monitoring have a positive influence on financial report fraud. Conversely, the variables of total accruals, CEO education, CEO duality, and political connections show a negative influence on financial report fraud. Corporate governance, as a moderating variable, is found to moderate only the relationship between external pressure and CEO duality on financial report fraud.